Heparin prophylaxis of gestational complications in women with Factor V Leiden mutation (GA genotype) - M. G. Nikolaeva; A. P. Momot; M. S. Zainulina; K. A. Momot; N. N. Yasafova (IRBIS LLC, 2018)
The aim of the study was to determine the efficacy of heparin prophylaxis in preventing pregnancy complications in patients with the manifested laboratory phenotype - resistance to activated protein C (APC-resistance with NR ≤ 0.49) Factor V Leiden mutation (GA genotype). Materials and methods. A single-center, randomized, controlled trial of 141 pregnant women - carriers of the FVL(1691)GA mutation with APC-resistance ≤ 0.49 was determined at a gestation age of 7-8 weeks. Of these, 70 patients were included in the main group (mean age 30.2 ± 4.7 years); after the confirmation of the APC-resistance at 7-8 weeks of gestation, these women received a 14 day low-molecular-weight heparin (LMWH) course at elevated prophylactic doses. The comparison group (71 pregnant women of 30.3 ± 3.9 years old) received no LMWH. Results. The heparin prophylaxis (started from 7-8 weeks of gestation) at elevated doses in carriers of the FVL(1691)GA mutation with pronounced APC-resistance reduced the absolute risk (ARR) of pre-eclampsia by 29.5% (ARR: 29.5; p = 0.0003; NTT: 3.4; 95% Cl: 2.356.12), the risk of fetal growth retardation by 23.8% (ARR: 23.8; p = 0.0016; NTT: 4.2; 95% Cl: 2.8-8.7) and the risk of induced premature birth by 12.6% (ARR: 12.6; p = 0.0242; NTT: 5.8; 95% Cl: 3.7-14.1). Conclusion. The administration of LMWH at prophylactic doses for 14 days is indicated in patients with a manifested subclinical (laboratory) phenotype (APC-resistance with NR ≤ 0.49) of the FVL(1691)GA mutation starting from the gestation period of 7-8 weeks. If necessary (with a value of NR ≤ 0.49), it is advisable to repeat the courses of heparin prophylaxis at 18-19 and 27-28 weeks of pregnancy.